Peran Media Sosial Sebagai Alat Propaganda Dalam Konflik Nagorno Karabakh Antara Armenia Dan Azerbaijan - Leyla Qarayeva; Yanyan Mochamad Yani; Widya Setiabudi (Universitas Komputer Indonesia, 2021)
The purpose of this paper is to explain how social media has become a new space for political discussion. The use of social media to report on conflicts, influence political perceptions, voice opinions about conflicts, and solicit public support around the world. As is the case with the Nagorno Karabakh ethnical conflict between Armenia and Azerbaijan which cannot be separated from social media. In this conflict, social media was also used to ask for public support around the world to side with one of the countries in the Nagorno Karabakh Conflict. This paper will also examine how governmental and non-governmental actors use social media as a tool of propaganda and how the international community is a part of spreading propaganda in the Nagorno Karabakh conflict. To help the author in the analysis process, at least the author uses several conceptual frameworks, including the role of social media in international relations, propaganda and identity conflicts in international relations. Keywords : Armenia; Azerbaijan; Ethnic Conflict; Nagorno Karabakh; Propaganda; Social Media